Effects of acute high-altitude exposure on heart rate variability: a systematic review and meta-analysis - Li, H.; Chen, X.; Huang, C.; Du, W. (Frontiers in Physiology, 2025)
Objective: This study aimed to systematically review and meta-analyze the effects of acute high-altitude exposure on heart rate variability (HRV), in order to elucidate the adaptive changes of the autonomic nervous system under high-altitude environments.